2021
DOI: 10.1007/s10750-021-04707-6
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics meets phylogenetics: new insights into the relationships among members of the genus Euthynnus (family Scombridae)

Abstract: Euthynnus (family Scombridae) is a genus of marine pelagic fish species with a worldwide distribution that comprises three allopatric species: E. alletteratus, E. affinis and E. lineatus. All of them targeted by artisanal and commercial fisheries. We analyzed 263 individuals from Atlantic and Pacific Oceans using two genetic markers, the mtDNA Control Region (350 bp) and nuclear calmodulin (341 bp). The results obtained challenge the phylogeny of this group. We found a deep genetic divergence, probably at spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Otolith shape analysis complements the genetics study already published on stock structure of this species [65]. The findings from our research on little tunny in the Eastern Atlantic have unveiled a new perspective.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Otolith shape analysis complements the genetics study already published on stock structure of this species [65]. The findings from our research on little tunny in the Eastern Atlantic have unveiled a new perspective.…”
Section: Discussionsupporting
confidence: 68%
“…Biological differences between both areas analyzed in this work have been poorly documented. In the genetic aspect, differentiating results could indicate the presence of separate species [65,66]. Olle et al (2022) observed that the mtDNA CR divergence between the two areas studied of E. alletteratus was nearly 20 times larger than the CR divergence between E. lineatus (Pacific Ocean) and E. affinis (Indian Ocean), and similar to the distance that separates E. alletteratus respectively from E. affinis and from E. lineatus [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Som, 2015). M t D N A i n t r o g r e s s i o n o c c u r s b e t w e e n s p e c i e s i n Scomberomorus (e.g., Morgan et al, 2013), and the possibility of incomplete lineage sorting in the youngest lineages in Scombridae has been suggested (Olléet al, 2022). Collette and Russo (1984), based on a cladistic analysis of 58 characters, identified six species groups in Scomberomorus, viz., the "sinensis group," which contains only S. sinensis; the "commerson species group" with S. commerson, S. niphonius, S. queenslandicus, and S. cavalla; the monotypic "munroi species group"; the "semifasciatus species group" with S. semifasciatus, S. plurilineatus, and S. lineolatus; the "guttatus species group" with S. guttatus, S. multiradiatus, and S. koreanus; and the "regalis species group" with S. regalis, S. tritor, S. maculatus, S. concolor, S. sierra, and S. brasiliensis.…”
Section: Discussion Phylogenetic Analysesmentioning
confidence: 99%
“…Additionally, a collection of 41 new sequences was added to the dataset and is available online under accession numbers MW574141-MW574181. All sequences of the dataset were generated following the procedures of Alvarado [31] and Ollé [32] and aligned with ClustalW [33] implemented in Geneious v7.1.9 [34]. Haplotypes were collapsed using DNAsp 6.12.03 [35] and assigned to the previously mentioned mitotype I and mitotype II based on reference sequences AB103467 and AB103468, respectively.…”
Section: Methodsmentioning
confidence: 99%